Extracorporeal membrane oxygenation for severe pediatric respiratory failure - Wong, Judith Ju-Ming; Cheifetz, Ira Marc; Lee, Jan Hau (Journal of Emergency and Critical Care Medicine; Vol 1 (July 2017): Journal of Emergency and Critical Care Medicine, 2017)
Respiratory extracorporeal membrane oxygenation (ECMO) utilises an extracorporeal circuit with an “artificial lung” (i.e., membrane oxygenator) to promote gas exchange and support life in cases of refractory hypoxemic and/or hypercarbic respiratory failure. Over the past few years, there has been a marked increase in the number of publications focused on evolving ECMO techniques and technologies. Initially used mainly in pulmonary parenchymal disease states, respiratory ECMO is increasingly being utilized to support children with severe respiratory failure from other diseases, such as upper airway obstruction, lower airway obstruction, foreign body aspiration and hyperviscosity syndromes. ECMO is also increasingly being described in children in whom ECMO was previously considered to be contraindicated. These patient groups include those with major genetic syndromes, malignancies, and post-transplantation. In this review, we examine the history and current evidence, including indications, duration of support, novel management approaches, and short- and long-term outcomes, in pediatric respiratory ECMO. We will also explore future potential challenges in further refining this life-saving technology for critically ill infants and children.